Accounting treatment analysis of rahn tasjily financing - Suhadak, Suhadak (Journal of Islamic Accounting and Finance Research, 2019)
Purpose - The purpose of this study was to describe the accounting treatment of rahn tasjily financing transactions carried out by BMT UGT Sidogiri Malang with PSAK 107 and the suitability of the transaction application with Fatwa DSN MUI DSN No.68/DSN-MUI/III/2008.Method - This study used descriptive qualitative method.Result - The research shows that the recognition and measurement of Ijarah transactions are in accordance with PSAK 107, but the presentation and disclosure are not appropriate. Recognition, measurement, and presentation of rahn tasjily financing transactions are in accordance with PAPSI, but the disclosure is not yet appropriate, and accordance with the application of Fatwa DSN MUI DSN No.68/DSN-MUI/III/2008.Implication - This study has an impact on the compliance of the institution in carrying out rahn tasjily financing of PSAK and Fatwa DSN MUI DSN No.68/DSN-MUI/III/2008.Originality - The focus of this study is the application of the determination and accounting treatment of Ijarah costs in rahn gold according to PSAK 107 and Fatwa DSN MUI DSN No.68/DSN-MUI/III/2008.